Antibacterial and catalytic performance of rGO-CNT-ZrO2 composite2 composite - Mizaj Shabil Sha (17714286) (2023)
In recent years, there has been a rise in public awareness regarding antibacterial properties and commercial opportunities for their use in the medical field. The current study describes the fabrication of a ternary composite, reduced graphene oxide-carbon nanotubes-zirconium oxide (rGO-CNT-ZrO2), and their potential applications for antimicrobial activity and catalytic degradation of neutral red, indigo carmine and eriochrome black-T dyes. In addition, the capability of nanocomposite for UV sensing was examined. These nanocomposites were made using the hydrothermal method. TEM, SEM, FTIR, TGA and XRD were used to characterise and investigate the properties of nanocomposite, and the disc diffusion technique was used to assess their antimicrobial activity. These findings suggest that the developed composite has excellent antimicrobial properties, which could be helpful in the pharmaceutical and medical industries. Other Information Published in: International Journal of Environmental Analytical Chemistry License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1080/03067319.2023.2230146